AN ANALYSIS OF THE THEME AND THEMATIC PROGRESSION OF NARRATIVE TEXTS IN ENGLISH TEST CONSTRUCTED BY TEACHER - Narita, Fanissa (2016)
This study entitled an Analysis of Theme and Thematic progression of Narrative Texts in English SummativeTest for Ninth Graders aims to find out Themes and Thematic progression patterns frequently reveal in Narrative text taken from the English tests for ninth graders used by the teacher. A descriptive-qualitative approach focusing on case study was employed in this study since only one school involved as the participant. The collected data were analyzed by using Theme system grounded from Systemic Functional Linguistics (SFL) theory (Halliday and Matthiessen, 2004). Firstly, the Narrative texts were selected following the theories of Genre by Eggins (2004) and Christie & Dewerianka (2008). Two out of three texts found in the test consisted of Complication, Evaluation, Resolution, Coda whereas one text didn't reveal Coda in the story. In terms of Theme choices, the dominant Theme appeared was Topical Theme, followed by Textual Theme and Interpersonal Theme. Meanwhile, the most frequent Thematic progression applied in the texts was Reiteration pattern which repeated the same Theme within clauses (Eggins, 2004). However, the results also showed some discontinuities in the Thematic progression of the two texts. Due to the discontinuities found, students are potentially hindered in discovering the point of the texts (Butt et al., 2000). Thus, the findings of the research suggested that the teacher should give more attention towards the materials given to students. Teacher is supposed to comprehend Theme system so that the analysis of text can be made to select a better test material.